Effect of neutron irradiation on the structure and strength of the SAV-1 aluminum alloy - Sh. A. Alikulov; S. A. Baytelesov; F. R. Kungurov; D. P. Tadjibaev; D. D. Tojiboev (Âderna Fìzika ta Energetika, 2022)
The aluminum alloy SAV-1 was studied before and after inducing the radiation damage by means of neutrons with the following values of doses: 1016 - 1018 n/сm2. The measurements were carried out by neutron diffraction methods to analyze the correlation of the structural state with the results of measurements of the strength of the sample obtained using a loading machine. It was found that the changes in the strength characteristics of aluminum alloys were associated with modifications at the grain boundary during irradiation of the samples. Thus, the obtained experimental data allows us to conclude that the SAV-1 alloy represents an interstitial solid solution, and the strength of the alloy changes nonlinearly depending on the radiation dose.